The Communication Strategy of Vertizone TV to Increase the Number of Subscriber - Fadhiliana, Feba; Suprabowo, Imam (Journal of Islamic Communication and Counseling, 2022)
Nowadays, YouTube is not only used for entertainment but also widely used for da’wa. One of them is Vertizone TV. Vertizone TV is one of the popular da’wa accounts in Indonesia and is relatively fast in increasing the number of subscribers. This research aimed at describing the communication strategy of Vertizone TV in increasing its while knowing the supporting and hindering factors of the strategy. This research applied a qualitative method with a descriptive approach. The data collection technique was through observation, interviews, and documentation. This research used the theory of Fred R.David, which states that a strategy process consists of 3 stages: planning, implementation, and evaluation. The findings revealed that the communication strategy of Vertizone TV in improving its number of subscribers involved the planning stage by setting vision and mission as well as for deciding the strategy for da’wa. For the implementation stage, Vertizone TV also had some strategies to get more viewers and subscribers. In the evaluation stage, Vertizone TV revaluated the implemented strategies whether they were effective and efficient. In addition, this evaluation stage was done to find out the pros and cons of implementing the strategy.